Українські церкви у США в обороні державності України (на матеріалах україномовної періодики діаспори) - Біловус, Леся Іванівна (My University, 2017)
Українська діаспора, успішно соціалізувавшись у США, набуває там політичної ваги і застосовує свій потенціал для захисту і реалізації її національних інтересів. Не останню роль у вищеназваних процесах відіграє українська церква. Дослідження присвячене аналізові матеріалів періодичних видань української діаспори США щодо оборони державності України українськими релігійними установами. Українська діаспора, створивши широку мережу україномовної періодики, надала українській церкві можливість не тільки виконувати свої прямі функції – душпастирство, а й особливого значення надавати формуванню національної ідентичності в середовищі української громади, стояти в обороні державності Української держави. The Ukrainian diaspora, having successfully socialized in the United States, gains political weight there and uses its potential to protect and realize its national interests. The Ukrainian church plays an important role in the above-mentioned processes. The research is devoted to the analysis of the materials from the Ukrainian Diaspora’s periodicals of the USA concerning the defense of Ukrainian statehood by Ukrainian religious institutions. The Ukrainian Diaspora, having created a wide network of Ukrainian-language periodicals, gave the Ukrainian church the opportunity not only to fulfill its direct function as a pastor, but also to attach special importance to the formation of a national identity within the Ukrainian community, to stand in the defense of the statehood of the Ukrainian state.
The Ukrainian religious institutions of the USA in the defense of the statehood of the Ukrainian state (on the materials of the Ukrainian Diaspora’s periodicals)
Keywords: Україномовна періодика, українська діаспора, українська церква, Україна; Ukrainian-language periodicals, Ukrainian Diaspora, Ukrainian Church, Ukraine